Los actantes en la narración tradicional boruca - Alvarado Chaves, Magda Lorena (Universidad de Costa Rica, 2015)
In this article 1 analyze ethica1 and didaáic tales taken from Leyendas y tradiciones de los borucas,(Constenla and Moroto: 1979) and four narraúves published by Constenla in 1986. The method usedis that of Greimas. The purpose of the study was 10 discover whether this method is applicable 10 traditionalstories belonging to non-European cultures. The method was indeed applicable, and it was discoveredthat in these stores the actant subject, which is positive in European folklore, is negative in thestories analyzed here and is regularly fused with the figure of the dispatcher. It as also established thatthe helper is practically absent and the opponent -who is negative in the European tradition- ispositive among the Borucas. Generally speaking, Borucan narratives are structurally quite simple.However there is frequent syncretism among the various actants.